Teaching quantitative courses to distance learners. - Mohd Nor, Nailul Murad; Abdul Karim, Mohamad Faisal
This paper describes how quantitative courses such as mathematics and statistic are taught at the Center for Distance Education, University Sains Malaysia (USH) in Malaysia. A combination of self-instructional printed materials and audio-conferencing are used to deliver study materials to students. Both delivery methods are known for their effectiveness and cheap to operate. Problems associated with these delivery methods are also highlighted.